PENGARUH PENANAMAN KARAKTER DISIPLIN DIRI TERHADAP KEPRIBADIAN ANAK DI LINGKUNGAN KELUARGA DESA SURABAYAN KECAMATAN SUKODADI KABUPATEN LAMONGAN - Haq, Devano Iqbal; Ghofur, Abd.; Rachma, Evi Aulia (Journal MISSY (Management and Business Strategy), 2024)
Discipline is a good value in character formation so that a person can organize himself to be a good person. The cultivation of self-discipline in the family environment is expected to be able to influence children's personalities for the better. This research was conducted in Surabayan Village, Sukodadi District, Lamongan Regency involving 52 parents who have children aged 7 to 9 years. The research method uses a quantitative approach method with the aim of determining the influence of self-discipline character cultivation on children's personality in the family environment of Surabayan Village, Sukodadi District, Lamongan Regency. The research instrument is in the form of a questionnaire with a Likert scale. In this study, the data analysis method used is a simple linear regression analysis. The results of the study showed that there was an effect of instilling the character of self-discipline in the family environment on the personality of children in Surabayan village, Sukodadi district, Lamongan district